Reconstructing peak discharges of historic floods of the river Ahr, Germany - Roggenkamp, Thomas; Herget, Jürgen (ERDKUNDE, 2014)
In the presented paper, peak discharges of historic floods in urbanized areas of different cities on the River Ahr in western Germany are reconstructed based on documentary sources from pre instrumental and the early instrumental period (1804–1937). Maximum water levels of five floods are denoted by flood-marks, with one of these events additionally documented by old photographs. The main challenge is the reconstruction of historic floodplain conditions and modifications influencing the cross-section area and the hydraulic roughness. In order to overcome this problem, a simple approach to estimate peak discharges of historic floods has been applied to the River Ahr. This approach includes a procedure for reconstructing the hydraulic parameters of the river channel and overflooded areas, coupled with an approach for the verification of estimated peak discharge reliability. Five reconstructed discharge maxima are presented. One of these events is well documented by numerous photographs, taken at different times of day, which allow the reconstruction of a hydrograph peak. The validation of the technique by comparison with recent gauged floods reveals results of adequate accuracy. The results show that reconstructed historic floods were partially larger than any gauged flood of the River Ahr.